2022
DOI: 10.3390/dj10010009
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Peripheral Ossifying Fibroma of the Mandible

Abstract: Peripheral ossifying fibroma (POF) is a benign localized lesion originating from gingival and alveolar oral mucosa. Its origin can be cells of periodontal ligament. The lesions usually develop in women in their twenties. POF is a complex clinical and histological diagnosis due to its shared characteristics with many other conditions. In this paper, we presented a case of an atypical peripheral ossifying fibroma (POF) in the left lateral part of the mandible in a 70-year-old male patient who had two semicircula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The patient in the current case report was 40 years of age, which is slightly older than common demographics of similar lesions that usually occur in females between the age of 20 and 30 years of age 39 . Osseous metaplasia starts as an inflammatory process of the periodontal cells and the periosteum that leads to metaplasia of the surrounding fibrous connective tissue and consequently dystrophic calcification and bone formation 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient in the current case report was 40 years of age, which is slightly older than common demographics of similar lesions that usually occur in females between the age of 20 and 30 years of age 39 . Osseous metaplasia starts as an inflammatory process of the periodontal cells and the periosteum that leads to metaplasia of the surrounding fibrous connective tissue and consequently dystrophic calcification and bone formation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Osseous metaplasia starts as an inflammatory process of the periodontal cells and the periosteum that leads to metaplasia of the surrounding fibrous connective tissue and consequently dystrophic calcification and bone formation 40 . Katanec et al demonstrated that high parathyroid hormone blood levels could be related to the development of calcified lesions such as peripheral ossifying fibroma that are very similar to the current reported lesion 39 . The current reported cases suffered from hypothyroidism and were taking Eltroxin 50 mg once per day.…”
Section: Discussionmentioning
confidence: 99%
“…POF development is associated with the periodontal ligament or periosteum, and its location is limited to the soft tissues positioned above the alveolar crest [ 5 ]. In our case, the manifestation of the lesion may be attributed to periodontal ligament remnants or periosteum since the patient is edentulous.…”
Section: Discussionmentioning
confidence: 99%
“…Additional terminology utilized to describe the POF include a peripheral cementifying fibroma, a peripheral fibroma with cementogenesis, a peripheral fibroma with osteogenesis, a peripheral fibroma with calcification, calcified or ossified fibrous epulis, and calcified fibroblastic granuloma [3,4]. The diagnosis of the POF is challenging due to its intricate clinical and histological features, which exhibit similarities with various different disorders, including fibroma, inflammatory fibrous hyperplasia, pyogenic granuloma, peripheral giant cell granuloma, and non-bone metastases of some cancers [5,6]. The aim of this study is to present a rare case of a maxillary POF, where the last two teeth of the mandible irritated the edentulous maxilla, triggering the formation of the POF.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 60% of POFs occur in the maxillary jaw, especially in the incisor-canine region. POF constitutes 9.6% of the gingival lesions, and it rarely occurs in the anterior mandibular region [ 3 ]. This case report describes an atypical presentation of POF in the anterior mandible in an adult male patient.…”
Section: Introductionmentioning
confidence: 99%